The Influence of Renal Function on In-Hospital Complications in Patients with ST-Elevation Myocardial Infarction - Petrosyan Harutyun; Hayrapetyan Hamlet; Torozyan Shahen; Tsaturyan Arsen; Buniatyan Vache; Sedrakyan Surik (Sciendo, 2022)
The goal of this study was to examine in-hospital complications in patients with acute ST-elevation myocardial infarction with a different renal function.